A Review on Modifications of Amniotic Membrane for Biomedical Applications - Dadkhah Tehrani, Fatemeh; Firouzeh, Arezoo; Shabani, Iman; Shabani, Azadeh (Frontiers in Bioengineering and Biotechnology, 2021)
Amniotic membrane (AM) is the innermost layer of the fetal placenta, which surrounds and protects the fetus. Its unique structure, in addition to its physical and biological properties, makes it a useful substance in many applications related to regenerative medicine. The use of this fantastic substance with a century-old history has produced remarkable results in vivo, in vitro, and even in clinical studies. While the intact or preserved AM is widely used for these purposes, the addition of further modifications to AM can be considered as a relatively new subject in its applications. These modifications are applied to improve AM properties, ease of handling, and durability. Here we will discuss the cases in which AM has undergone additional modifications besides the required processes for sterilization and preservation. In this article, we have categorized these modifications and discussed their applications and results.